2021
DOI: 10.1039/d0cp06266a
|View full text |Cite
|
Sign up to set email alerts
|

Third dissociation constant of phosphoric acid in H2O and D2O from 75 to 300 °C at p = 20.4 MPa using Raman spectroscopy and a titanium-sapphire flow cell

Abstract: The first reported Raman spectra and ionization constants for the phosphate ion in H2O and D2O above 50 °C quantify deuterium isotope effects under hydrothermal conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…This expression demonstrated that changes in hydrogen bonding and the water coordination number at high temperature along with the drop in the light and heavy water dielectric constants would be expected to result in an increase in the Δp K a,m as it approaches the solvent critical points. 12 This prediction is consistent with the trend observed in the deuterium isotope effect on the bisulfate ionization reaction measured in this work, and by Yacyshyn et al , 22 further evidencing the validity of these results over those previously reported by Lietzke and Stoughton. 5…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This expression demonstrated that changes in hydrogen bonding and the water coordination number at high temperature along with the drop in the light and heavy water dielectric constants would be expected to result in an increase in the Δp K a,m as it approaches the solvent critical points. 12 This prediction is consistent with the trend observed in the deuterium isotope effect on the bisulfate ionization reaction measured in this work, and by Yacyshyn et al , 22 further evidencing the validity of these results over those previously reported by Lietzke and Stoughton. 5…”
Section: Discussionsupporting
confidence: 92%
“…The deuterium isotope effect on chemical equilibrium constants has been reported in the literature for very few chemical systems at high temperatures. 5–12 As was described in the review by Laughton and Robertson, 2 a typical deuterium isotope effect is 0.2 > Δp K a,m > 1.0 at 25 °C with the general trend that the deuterium isotope effect increases with the acid p K a value. 4,76 As the temperature increases, the deuterium isotope effect on an acid ionization constant may increase or decrease, and the relative order of the effect between different acids is not preserved.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is once again important to note that the values of these rate constants have been shown to depend strongly on the local reaction environment. , For this reason, there is variance in the measured values for these rate constants. Additionally, these rate constants are dependent on the local electric field due to the second Wien effect (as discussed in section )a phenomenon which becomes particularly relevant in bipolar membranes or in the electrical double layer. Proper models of electrochemical synthesis should aim to provide sensitivity analyses on the values of these rate parameters to account for the inconsistency in experimentally reported values.…”
Section: General Aspects and Equationsmentioning
confidence: 99%